Investigating the Impact of Oil Price and Exchange Rate Uncertainty on Stock Return using Whitening Linear Transformation and Vector Autoregressive Model - Farahani, Mohammad; Hanzaee, Alireza Heidarzadeh (The Indonesian Capital Market Review, 2018)
This study aims at investigating the impact of oil price and exchange rate uncertainty on stock returns in Tehran Securities Exchange (TSE). To this end, "oil price uncertainty" and "exchange rate uncertainty" are considered as independent variables and "return on stocks" as the dependent variable. Daily data on the price of heavy oil, official exchange rate and Tehran Exchange Price Index (TEPIX) are used from 1 January 2002 to 31 December 2012. To evaluate the impact of oil price and exchange rate uncertainty on stock returns, the uncertainty is measured using Whitening Linear Transformation method and is estimated using the Vector Auto Regressive model. Results of the estimations of the model show that there is a significant relation between the uncertainty of oil price and stock returns and another between the uncertainty of exchange rate and stock returns. Thus, the hypothesis of this study are confirmed by the error level of 0.05